Molecular dynamics simulations of solid sulphur hexafluoride - Hua, Lu (The University of Edinburgh, 1992)
This thesis is a study of a molecular crystal SF⁶ through the molecular dynamics(MD) method. Solid SF⁶ has a plastic phase below its melting point and in this phase the interactions between the molecules are highly anharmonic and the orientations of the molecules are highly disordered. At even lower temperatures, the substance has a truly crystalline phase which exhibits, according to our MD simulation, some highly anharmonic properties such as molecular reorientation especially when the temperature is near the plastic -crystal transition point.

In the simulation, a simple Lennard -Jones potential function is used to represent the interactions between the molecules. So far, it has been found that this model can give results which are well in agreement with experiments in both the plastic and the crystalline phase. The agreement between the lattice parameters from the simulation and from neutron experiments is very good. The plastic -crystal phase transition and melting are observed in the simulation. The melting point for a bulk sample is found to be 23% higher than the experimental values but the melting point estimated from the surface -initiated melting is found to be closer to the experimental value. In the study of the low- temperature phase we have found that the thermal motions of the molecules are very diferent for the molecules occupying the two different symmetry sites of the monoclinic structure. Highly anisotropic patterns of the molecular movements have also been revealed.

In order to study the plastic -crystal phase transition, a constant- pressure MD method is used to ensure the smooth transitions between single -crystals. Through the use of this method, we have found that in the search for new crystalline structures the phase transitions are not necessarily between single crystals - crystallites with certain orientation may prevail resulting in a large crystal with domain structures.

SF⁶ is a substance which has not been fully studied through experiments. This offers us an opportunity to use the MD method to predict some of its properties to guide experiments. In this thesis, we present the work on the use the fluctuations of the simulated system to calculate the heat capacity and the elastic constants.